A support programme for secondary prevention in patients with transient ischaemic attack and minor stroke (INSPiRE-TMS): an open-label, randomised controlled trial. Issue 1 (January 2020) - Ahmadi, Michael; Laumeier, Inga; Ihl, Thomas; Steinicke, Maureen; Ferse, Caroline; Endres, Matthias; Grau, Armin; Hastrup, Sidsel; Poppert, Holger; Palm, Frederick; Schoene, Martin; Seifert, Christian L; et al.
Summary: Background: Patients with recent stroke or transient ischaemic attack are at high risk for a further vascular event, possibly leading to permanent disability or death. Although evidence-based treatments for secondary prevention are available, many patients do not achieve recommended behavioural modifications and pharmaceutical prevention targets in the long-term. We aimed to investigate whether a support programme for enhanced secondary prevention can reduce the frequency of recurrent vascular events. Methods: INSPiRE-TMS was an open-label, multicentre, international randomised controlled trial done at seven German hospitals with acute stroke units and a Danish stroke centre. Patients with non-disabling stroke or transient ischaemic attack within 2 weeks from study enrolment and at least one modifiable risk factor (ie, arterial hypertension, diabetes, atrial fibrillation, or smoking) were included. Computerised randomisation was used to allocate patients (1:1) either to the support programme in addition to conventional care or to conventional care alone. The support programme used feedback and motivational interviewing strategies with eight outpatient visits over 2 years aiming to improve adherence to secondary prevention targets. The primary outcome was the composite of major vascular events consisting of stroke, acute coronary syndrome, and vascular death, assessed in the intention-to-treat population (all patients who underwent randomisation, did not withdraw study participation, and had at least one follow-up). Outcomes were assessed at annual follow-ups using time-to-first-event analysis. All-cause death was monitored as a safety outcome. This trial is registered with ClinicalTrials.gov, NCT01586702 . Findings: From Aug 22, 2011, to Oct 30, 2017, we enrolled 2098 patients. Of those, 1048 (50·0%) were randomly assigned to the support programme group and 1050 (50·0%) patients were assigned to the conventional care group. 1030 (98·3%) patients in the support group and 1042 (99·2%) patients in the conventional care group were included in the intention-to-treat analysis. The mean age of analysed participants was 67·4 years and 700 (34%) were women. After a mean follow-up of 3·6 years, the primary outcome of major vascular events had occurred in 163 (15·8%) of 1030 patients of the support programme group and in 175 (16·8%) of 1042 patients of the conventional care group (hazard ratio [HR] 0·92, 95% CI 0·75–1·14). Total major vascular event numbers were 209 for the support programme group and 225 for the conventional care group (incidence rate ratio 0·93, 95% CI 0·77–1·12; p=0·46) and all-cause death occurred in 73 (7·1%) patients in the support programme group and 85 (8·2%) patients in the conventional care group (HR 0·85, 0·62–1·17). More patients in the support programme group achieved secondary prevention targets (eg, in 1-year-follow-up 52% vs 42% [p<0·0001] for blood pressure, 62% vs 54% [p=0·0010] for LDL, 33% vs 19% [p<0·0001] for physical activity, and 51% vs 34% [p=0·0010] for smoking cessation). Interpretation: Provision of an intensified secondary prevention programme in patients with non-disabling stroke or transient ischaemic attack was associated with improved achievement of secondary prevention targets but did not lead to a significantly lower rate of major vascular events. Further research is needed to investigate the effects of support programmes in selected patients who do not achieve secondary prevention targets soon after discharge. Funding: German Federal Ministry of Education and Research, Pfizer, and German Stroke Foundation.